2018
DOI: 10.1002/ijc.31627
|View full text |Cite
|
Sign up to set email alerts
|

High turnover of extracellular matrix reflected by specific protein fragments measured in serum is associated with poor outcomes in two metastatic breast cancer cohorts

Abstract: Increased extracellular matrix (ECM) formation and matrix metalloprotease (MMP)-mediated ECM degradation are parts of tumorgenesis and generates collagen fragments that are released into circulation. We evaluated the association of specific collagen fragments measured in serum with outcomes in two independent metastatic breast cancer (MBC) cohorts. ELISAs were used to measure C1M (MMP-generated type I collagen fragment), C3M (MMP-generated type III collagen fragment), C4M (MMP-generated type IV collagen fragme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
39
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 42 publications
(41 reference statements)
1
39
0
Order By: Relevance
“…been associated with poor outcomes in breast cancer and malignant melanoma. 27,28 However, PRO-C3's role in HCC remains to be established. The PRO-C3 biomarker does not differentiate between single stranded or cross-linked N-terminal pro-peptides ( Figure 1).…”
Section: Dovepressmentioning
confidence: 99%
See 1 more Smart Citation
“…been associated with poor outcomes in breast cancer and malignant melanoma. 27,28 However, PRO-C3's role in HCC remains to be established. The PRO-C3 biomarker does not differentiate between single stranded or cross-linked N-terminal pro-peptides ( Figure 1).…”
Section: Dovepressmentioning
confidence: 99%
“…Multivariate Cox proportional-hazards regression was used to assess the independent predictive value of PC3X and AFP adjusted for the above mentioned clinical variables. For statistical purposes, PC3X and PRO-C3 levels under the 75th percentile cut-point were used as a reference to calculate the HR for patients with levels above the 75th percentile, which was based on the data distribution and previous studies 27,28. AFP levels under 20 IU/mL were used as a reference to calculate the HR for patients with elevated AFP levels 32.…”
mentioning
confidence: 99%
“…The most dominant proteins in the ECM are the collagens, of which there are 28 different types [7]. Our research group has previously demonstrated that collagens and other ECM proteins can be valuable as non-invasive biomarker tools in different cancer forms [8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Although HA and collagen expression in the TME are considered prognostic biomarkers, there are no/few studies examining serum concentrations of HA and type III collagen in patients with PC. Previous studies conducted in other malignancies have shown a negative correlation between serum HA and outcome and serum collagen fragments and outcome . The aim of this biomarker study was to investigate the clinical utility of serum HA and propeptide of type III collagen (PRO‐C3) in patients with PC.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies conducted in other malignancies have shown a negative correlation between serum HA and outcome [40][41][42][43][44][45] and serum collagen fragments and outcome. 33,[46][47][48] The aim of this biomarker study was to investigate the clinical utility of serum HA and propeptide of type III collagen (PRO-C3) in patients with PC.…”
Section: Introductionmentioning
confidence: 99%